An experimental study on the drying-out ability of highly insulated wall structures with built-in moisture and rain leakage - Viljanen, Klaus; Lu, Xiaoshu (MDPI, 2019)
The recent research on highly insulated structures presents controversial conclusions on risks in moisture safety. This paper addresses these controversial issues through investigating the hygrothermal performance of energy efﬁcient envelope structures under high moisture loads. The experiments consist of built-in moisture and rain leakage tests in mineral wool insulated structures. A heat and moisture transfer simulation model is developed to examine the drying-out ability in both warm and cold seasons. The results show that the energy efﬁcient structures have an excellent drying out ability against built-in and leakage moisture. The difference in the drying ability is limited compared to conventional structures. A critical leakage moisture amount reaching the insulation cavity for a wood frame wall is determined to be between 6.9–20.7 g in a single rain event occurring every other day. Further research is required to target highly insulated structures, particularly addressing water vapor diffusion and convection.
Keywords: hygrothermal behaviour; built-in moisture; leakage; wood frame wall; fi=Energiatekniikka|en=Energy Technology|